For some integers a and b the function f ( x ) = a x + b has the properties that f ( f ( 0 ) ) = 0 and f ( f ( f ( 4 ) ) ) = 9 , find f ( f ( f ( f ( 1 0 ) ) ) ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Thank you for sharing your solution.
if f ( f ( 0 ) ) = 0 , then f ( x ) must either have reflective symmetry about the line y = x , or be of the form f ( x ) = k x for some k .
Case 1:
If there is reflective symmetry about y = x , then f ( f ( x ) ) = x . Therefore f ( f ( f ( f ( x ) ) ) ) = f ( f ( x ) ) = x , so f ( f ( f ( f ( 1 0 ) ) ) ) = 1 0 .
Case 2:
if y = k x , then f ( f ( f ( x ) ) ) = k 3 x . The condition f ( f ( f ( 4 ) ) ) = 9 implies 4 k 3 = 9 . However, this means k is not an integer so we reject this case.
Thus f ( f ( f ( f ( 1 0 ) ) ) ) = 1 0
Thank you for sharing your solution.
That's a nice way! I solved f(x) = - x + 5 first, but that's more work.
Problem Loading...
Note Loading...
Set Loading...
f ( x ) f ( f ( 0 ) ) f ( a ( 0 ) + b ) f ( b ) a b + b ( a + 1 ) b = a x + b = 0 = 0 = 0 = 0 = 0
⟹ { b = 0 a = − 1
If b = 0 , then f ( x ) = a x , then we have f ( f ( f ( 4 ) ) ) = f ( f ( 4 a ) ) = f ( 4 a 2 ) = 4 a 3 = 9 , ⟹ a = 3 4 9 not an integer.
Therefore, the solution is a = − 1 and f ( x ) = b − x , and we have f ( f ( f ( 4 ) ) = f ( f ( b − 4 ) ) = f ( b − b + 4 ) = f ( 4 ) = b − 4 = 9 , ⟹ b = 1 3 and f ( x ) = 1 3 − x .
Now we have
f ( f ( f ( f ( 1 0 ) ) ) ) f ( f ( f ( 3 ) ) ) f ( f ( 1 0 ) ) f ( 3 ) = f ( f ( f ( 1 3 − 1 0 ) ) ) = f ( f ( 1 3 − 3 ) ) = f ( 1 3 − 1 0 ) = 1 3 − 3 = 1 0